Alay alab a policy formation advocacy campaign for the comfort women of the Philippines - Doydora, Daniel AJR G. (College of Fine Arts, University of the Philippines Diliman, 2016)
This study aimed to investigate the issues and legal parameters of the comfort women in the Philippines and to find the vital solution gearing towards a policy formation in favor of the women's group by the government. This study was conducted through a collection and comprehensive analysis of different written materials on the subject of the comfort women. A series of interviews with point-to experts in the fields of Human Rights and Public policy-making were done to have a preliminary understanding of the concepts encircling the comfort women issue. Based on the research and following the policy-making process, a visual communication effort could be essential for this policy formation. This effort aimed to strengthen the position of the comfort women as war victims and garner a wider audience and support to trigger public discussion and pressure the government to endorse their claims to international courts. This could be achieved through an overhauling of the newly formed support group. Pamana's, organisational identity and pushing the advocacy campaign "Alay Alab" under new organisation.